2006
DOI: 10.1074/jbc.m600435200
|View full text |Cite
|
Sign up to set email alerts
|

Expression Cloning and Periplasmic Orientation of the Francisella novicida Lipid A 4′-Phosphatase LpxF

Abstract: Francisella tularensis and related intracellular pathogens synthesize lipid A molecules that differ from their Escherichia coli counterparts. Although a functional orthologue of lpxK, the gene encoding the lipid A 4-kinase, is present in Francisella, no 4-phosphate moiety is attached to Francisella lipid A. We now demonstrate that a membrane-bound phosphatase present in Francisella novicida U112 selectively removes the 4-phosphate residue from tetra-and pentaacylated lipid A molecules. A clone that expresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
143
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(148 citation statements)
references
References 68 publications
(111 reference statements)
5
143
0
Order By: Relevance
“…Here, we demonstrate that inactivation of the periplasmic phosphatase, previously shown to be involved in Francisella lipid A 4Ј dephosphorylation in vitro (16), results in a mutant that retains the 4Ј-phosphate moiety in its lipid A in living cells (Figs. 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we demonstrate that inactivation of the periplasmic phosphatase, previously shown to be involved in Francisella lipid A 4Ј dephosphorylation in vitro (16), results in a mutant that retains the 4Ј-phosphate moiety in its lipid A in living cells (Figs. 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of the neutrophil bactericidal activity is attributed to the repertoire of secreted cationic antimicrobial peptides, such as the defensins (23). Because structural modifications that reduce the net negative charge of lipid A have been shown to alter susceptibility to cationic antimicrobial peptides (24)(25)(26), we compared the sensitivity of the mutant and wild-type with the cationic antimicrobial peptide polymyxin B (16,27). Employing a disk diffusion assay, we observed that wild-type F. novicida U112 bacteria are highly resistant to polymyxin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yp strain KIM6+ was grown in Luria broth (pH 7.4) at 37°C with aeration and harvested in the late exponential phase referred to as Yp wild type (Yp_WT) [24]. Lipid A C-1 and C-4' phosphatase, LpxE and LpxF, respectively, have been expression cloned in Fn [25]. The individual plasmids with the structural genes of LpxE or LpxF and an ampicillin resistance gene were incorporated into KIM6+ cell via electroporation [11].…”
Section: Methodsmentioning
confidence: 99%